Accuracy of trained rural ophthalmologists versus non-medical image graders in the diagnosis of diabetic retinopathy in rural China. Issue 11 (4th July 2018) - McKenna, Martha; Chen, Tingting; McAneney, Helen; Vázquez Membrillo, Miguel Angel; Jin, Ling; Xiao, Wei; Peto, Tunde; He, Mingguang; Hogg, Ruth; Congdon, Nathan
Abstract : Background/aims: To determine the diagnostic accuracy of trained rural ophthalmologists and non-medical image graders in the assessment of diabetic retinopathy (DR) in rural China. Methods: Consecutive patients with diabetes mellitus were examined from January 2014 to December 2015 at 10 county-level facilities in rural Southern China. Trained rural ophthalmologists performed a complete eye examination, recording diagnoses using the UK National Diabetic Eye Screening Programme (NDESP) classification system. Two field, mydriatic, 45° digital photographs were made by nurses using NDESP protocols and graded by trained graders with no medical background using the NDESP system. A fellowship-trained retina specialist graded all images in masked fashion and served as reference standard. Results: Altogether, 375 participants (mean age 60±10 years, 48% men) were examined and 1277 images were graded. Grader sensitivity (0.82–0.94 (median 0.88)) and specificity (0.91–0.99 (median 0.98)), reached or exceeded NDESP standards (sensitivity 80%, specificity 95%) in all domains except specificity detecting any DR. Rural ophthalmologists' sensitivity was 0.65–0.95 (median 0.66) and specificity 0.59–0.95 (median 0.91). There was strong agreement between graders and the reference standard (kappa=0.84–0.87, p<0.001) and weak to moderate agreement between rural doctors and the reference (kappa=0.48–0.64, p<0.001). Conclusion: This is the first study of diagnostic accuracy in DR grading among non-medical graders or ophthalmologists in low-income and middle-income countries. Non-medical graders can achieve high levels of accuracy, whereas accuracy of trained rural ophthalmologists is not optimal.